Two Conceptions of Economics and Maximization - Crespo, Ricardo Fernando (2013)
Economics has evolved from a ‘domain-focused’ conception, i.e. the study of specific kinds of human activities, to a ‘scarcity-based’ conception, i.e. the study of a particular approach to all human choices. It thus enlarged its domain and narrowed its perspective: instrumental maximising. This paper maintains that economics should be domain focused, with a core of scarcity-based analysis of its domain, integrated into a broader analysis. It also holds that the scarcity-based analysis of realities falling outside the economic domain is not economics, but rather a social science broader in respect to the field but narrower in respect to the analysis, and thus partial in its conclusions. Section 2 introduces these versions of economics, Section 3 links them to specific conceptions of rationality, Section 4 provides arguments for the paper’s thesis and Section 5 deals with two related versions of maximisation and argues for adopting one of them.